Buna-N rubber bright-surface rubber plug not easy to dirty mold and preparation method thereof

By adopting specific formulas of Dingqing rubber glossy rubber plugs and molded vulcanization molding technology, the problems of unenvironmental materials, pollution and toxic gases in the production process of existing mirror rubber plugs are solved, and an efficient and environmentally friendly production process is achieved, and the sealing performance of the product is improved.

CN119708660APending Publication Date: 2025-03-28WUXI PERUN RUBBER & PLASTIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411729622.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing mirror rubber plugs have unecotched materials during the production process, and polluted and toxic gases are generated during the vulcanization process, which affects production efficiency and workers' health.

Method used

The formula of shiny rubber shiny rubber plug that is not easy to be dirty is adopted, including specific proportions of shiny rubber, styrene butadiene rubber, activated zinc oxide, stearic acid, vulcanization accelerator, vulcanization agent and other components. It is kneaded and opened and treated with molded vulcanization molding technology.

Benefits of technology

Reduces foreign matter on the surface of the mold, reduces the number of times workers wipe the mold, improves production efficiency, reduces the emission of toxic gases, and the product has good sealing performance in oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708660A_ABST
    Figure CN119708660A_ABST
Patent Text Reader

Abstract

The invention discloses a Buna-N rubber bright-surface rubber plug not easy to dirty a mold, and the Buna-N rubber bright-surface rubber plug is prepared from the following raw materials in parts by weight: 20-30 parts of a rubber material, comprising the following components: 90 to 95 parts of nitrile rubber 3305, 5 to 10 parts of butadiene styrene rubber 1502, 4 to 5 parts of activated zinc oxide, 1 to 1.5 parts of stearic acid, 0.5 to 1 part of an anti-aging agent RD, 0.5 to 1 part of an anti-aging agent 4010NA, 0.5 to 1.5 parts of semi-refined paraffin, 2.5 to 3.5 parts of a vulcanization accelerator, 2.0 to 2.5 parts of a vulcanizing agent S-80, 10 to 20 parts of a carbon black reinforcing agent N330, 35 to 45 parts of semi-reinforced carbon black, 8 to 12 parts of a white carbon black reinforcing agent, 10 to 20 parts of calcined kaolin, 10 to 20 parts of light calcium carbonate and 15 to 25 parts of a softening agent ATBC. The mold wiping frequency and the mold brushing frequency of workers are reduced, the labor intensity of the workers is reduced, the production efficiency is improved, and meanwhile emission of poisonous gas is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to an environmentally friendly nitrile rubber bright surface rubber plug which is not easy to get a dirty mold and a preparation method thereof. Background Art

[0002] Nitrile rubber is also known as butadiene-acrylonitrile rubber, abbreviated as NBR. Nitrile rubber is mainly produced by low-temperature emulsion polymerization. The introduction of cyano groups with higher polarity into nitrile rubber improves the stability of the rubber structure, making nitrile rubber more resistant to non-polar oils, second only to polysulfide rubber and fluororubber. Nitrile rubber contains acrylonitrile structure, which reduces the degree of unsaturation of the molecule. Due to the strong electron-withdrawing ability of the cyano group, the hydrogen at the allyl position is relatively stable, so its heat resistance is better than that of general-purpose rubbers such as natural and styrene-butadiene rubber; the polarity of nitrile rubber increases the intermolecular force and improves wear resistance; the cyano group of nitrile rubber and the trans-1,4 structure in the molecule make its structure compact, the air permeability is low, and the air tightness is improved; because nitrile rubber has both good oil resistance and maintains good rubber properties. Therefore, it is widely used in various oil-resistant products. Nitrile rubber with high acrylonitrile content is generally used for products that are in direct contact with oils and have relatively high oil resistance requirements, such as oil seals, oil hoses, chemical container linings, gaskets, etc.

[0003] The functions of various rubber plugs used in sewing machine heads are: first, to seal the machine head oil; second, to plug various screw holes for aesthetic purposes.

[0004] At present, there are problems with the mirror rubber plugs produced: a. The materials are not environmentally friendly and do not meet the EU REACH standards. b. The pollutants generated during the vulcanization of nitrile rubber include sulfur-containing compounds (such as H2S, SO2, mercaptans, sulfides), dust (such as carbon black), hydrocarbons (such as alkanes, olefins, hydrocarbons, aromatic hydrocarbons) and oxygen-containing organic matter (such as alcohols, phenols, aldehydes, ketones, organic acids, etc.). The volatilization of these small molecules will cause the mold surface to become dirty. During the production of rubber plugs, a layer of dirt will appear on the mirror mold surface for each vulcanized product, and the workers need to wipe the mold with cotton cloth once, which wastes time and reduces production efficiency. c. During the vulcanization production process of rubber plugs, some toxic VOC gases will be generated, which will affect the health of the operators. Summary of the invention

[0005] In view of the problems mentioned in the background technology, the purpose of the present invention is to provide a formula and preparation method of a nitrile rubber bright surface rubber plug that is not easy to dirty the mold, so as to reduce the number of times workers wipe and brush the mold, reduce the labor intensity of workers, improve production efficiency, and at the same time reduce the emission of toxic gases.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions:

[0007] A nitrile rubber bright surface rubber plug which is not easy to get a dirty mold. The raw materials of the nitrile rubber bright surface rubber plug include the following components by weight:

[0008]

[0009] Preferably, the nitrile rubber 3305 is produced by the synthetic rubber plant of Lanzhou Petrochemical Company.

[0010] Preferably, the active zinc oxide is nano-active ZNO produced by Luoyang Lantian.

[0011] Preferably, the stearic acid is SA-1801 from Wilmar Oil & Fats.

[0012] Preferably, the vulcanization accelerator is a mixture of N-cyclohexyl-2-benzothiazolylsulfonamide (CZ), dibenzothiazyl disulfide (DM), and tetramethylthiuram disulfide TMTD produced by Weilin New Materials Technology Co., Ltd. in a weight ratio of 5:3:1.

[0013] Preferably, the vulcanizing agent is granulated sulfur from Zhongshan Hanxin Rubber and Plastic Material Factory: S-80GEF150.

[0014] Preferably, the vulcanization accelerator is a combination of one or more thiazole, thiuram or quinone accelerators.

[0015] Preferably, the antioxidant RD and antioxidant 4010NA are produced by Sinopec Nanjing Chemical Industry Co., Ltd.

[0016] Preferably, the semi-refined paraffin wax is produced by China National Petroleum Corporation.

[0017] Preferably, the carbon black reinforcing agent N330 is produced by Shandong Bio Carbon Black.

[0018] Preferably, the white carbon black is Hengsil-955 produced by Wuxi Hengheng White Carbon Black Co., Ltd.

[0019] Preferably, the semi-reinforcing carbon black is semi-reinforcing carbon black 774 produced by Kashgar Derik.

[0020] Preferably, the calcined kaolin is produced by China Kaolin Corporation.

[0021] Preferably, the light calcium carbonate is produced by Xuancheng Zhuofeng New Materials.

[0022] Preferably, the softener is acetyl tributyl citrate ATBC produced by Jiangsu Raymond New Materials Co., Ltd.

[0023] A method for preparing a nitrile rubber bright surface rubber plug which is not easy to get a dirty mold, comprising the following steps:

[0024] (1) Use a rubber cutting machine to cut the nitrile rubber 3305 and styrene butadiene rubber 1502 and set aside;

[0025] (2) Add 90-95 parts of nitrile rubber 3305 and 5-10 parts of styrene butadiene rubber 1502 to the kneading machine, and after plasticating for 60 seconds, lift the pressing mass, add 4-5 parts of active zinc oxide, 1-1.5 parts of stearic acid, 0.5-1.0 parts of antioxidant RD, 0.5-1.0 parts of antioxidant 4010NA, 0.5-1.5 parts of semi-refined paraffin, and 2.5-3.5 parts of vulcanization accelerator. After kneading for 60 seconds, lift the upper pressing mass, and add 10-20 parts of carbon Black reinforcing agent N330, 35-45 parts of semi-reinforcing carbon black, 8-12 parts of white carbon black, 10-20 parts of calcined kaolin, 10-20 parts of light calcium carbonate, 15-25 parts of softener, knead for 60 seconds, raise the pressure weight, after the rubber material is agglomerated, raise the pressure weight once, knead for 60 seconds, clean the dust at the feeding port, add the pressure weight, raise the pressure weight twice in the middle, until the temperature of the mixing chamber rises to 130℃, and then automatically discharge the material, the total time is about 8-10 minutes;

[0026] (3) the rubber material of step (2) is discharged on a 22-inch open mill, the roller distance is adjusted to 2-4 mm, and the material is thinned three times; it is conveyed by a conveyor belt and cooled to below 90° C., 2-2.5 parts of a vulcanizing agent are added on a 24-inch open mill, the roller distance is adjusted to 1-2 mm, and the material is thinned three times. After making two triangular packages, the material is placed on a sheet with a thickness of 6-8 mm and cooled;

[0027] (4) Take the sample and perform sulfurization at 165℃×8min, test the test piece at 165℃×6min, cool for 16h, and test the physical properties; after meeting the basic requirements of physical properties, according to the thickness required by the mold, 18-inch open mill produces 3-5mm sheets;

[0028] (5) Cut the semi-finished product into a shape according to the width of the semi-finished product required for molding using a strip cutter, and weigh the semi-finished product using an electronic scale;

[0029] (6) Add the semi-finished product into the mold and start vulcanization molding; the conditions for compression vulcanization molding are temperature 165°C, time 6 minutes, and pressure 18 MPa.

[0030] The present invention mainly has the following beneficial effects:

[0031] (1) The mirror-surface mold surface of the present invention is not prone to residual foreign matter. During the vulcanization production process of the product, there is no need to wipe the mold cavity of the mirror-surface mold with cotton cloth. The surface of the mold cavity remains clean for a long period of time without any stains.

[0032] (2) With the formula design of the present invention, when the product comes into contact with oil, its volume expands slightly, so that the plug and the hole can be tightly sealed, and the plug is not easy to fall off.

[0033] (3) The active zinc oxide and stearic acid in the formula of the present invention are active agents, which accelerate the vulcanization speed and increase the crosslinking density; the vulcanizing agent acts as a crosslinking agent, increases the tensile strength of the rubber compound, and improves the tensile strength; the vulcanization accelerator can accelerate the vulcanization speed and acts as a vulcanizing aid; the antioxidants RD and 4010NA play a role in heat aging resistance and extend the service life; N330 plays a role in reinforcing agent, and the semi-reinforcing carbon black plays a semi-reinforcing role, both of which increase the tensile strength of the rubber compound and increase the hardness of the rubber compound; white carbon black not only plays a role in reinforcing agent and improving the tear strength, but the most important role of the present invention is that white carbon black has an adsorption effect, which increases the mold size and is not easy to be contaminated; the role of clay and light calcium filler is to reduce the cost of the rubber compound and make the rubber sheet smoother; the softener ATBC can improve the operability of the mixed rubber and adjust the hardness of the rubber compound. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a photograph of the vulcanized product prepared in Example 1 of the present invention;

[0035] Figure 2 It is a photograph of the vulcanized product obtained in the comparative example of the present invention. DETAILED DESCRIPTION

[0036] Embodiment 1

[0037] A method for preparing a nitrile rubber bright surface rubber plug which is not easy to get a dirty mold, comprising the following steps:

[0038] (1) Use a rubber cutting machine to cut the nitrile rubber 3305 and styrene butadiene rubber 1502 and set aside;

[0039] (2) Add 90 parts of nitrile rubber 3305 and 10 parts of styrene butadiene rubber 1502 to the kneading machine. After plasticating for 60 seconds, lift the pressing mass and add 4 parts of active zinc oxide, 1 part of stearic acid, 0.5 parts of antioxidant RD, 0.5 parts of antioxidant 4010NA, 0.5 parts of semi-refined paraffin, and 2.5 parts of vulcanization accelerator. After kneading for 60 seconds, lift the upper pressing mass and add 10 parts of carbon black reinforcing agent N3 30, 35 parts of semi-reinforced carbon black, 8 parts of white carbon black, 10 parts of calcined kaolin, 10 parts of light calcium carbonate, 15 parts of softener, knead for 60 seconds, raise the pressure weight, after the rubber material is agglomerated, raise the pressure weight once, knead for 60 seconds, clean the dust at the feeding port, add the pressure weight, raise the pressure weight twice in the middle, until the temperature of the mixing chamber rises to 130℃, and then automatically discharge the material, the total time is about 8 minutes;

[0040] (3) the rubber material of step (2) is discharged on a 22-inch open mill, the roller distance is adjusted to 3 mm, and the material is thinned three times; it is conveyed by a conveyor belt and cooled to below 90° C., 2 parts of a vulcanizing agent are added on a 24-inch open mill, the roller distance is adjusted to 1 mm, and the material is thinned three times. After making two triangular bags, the material is placed on a sheet with a thickness of 7 mm and cooled;

[0041] (4) Take the sample and perform sulfurization at 165℃×8min, test the test piece at 165℃×6min, cool for 16h, and test the physical properties; after meeting the basic requirements of physical properties, according to the thickness required by the mold, 18-inch open mill produces 3-5mm sheets;

[0042] (5) Cut the semi-finished product into a shape according to the width of the semi-finished product required for molding using a strip cutter, and weigh the semi-finished product using an electronic scale;

[0043] (6) Add the semi-finished product into the mold and start vulcanization molding; compression vulcanization molding conditions: temperature 165°C, time 6 minutes, pressure 18 MPa.

[0044] In this embodiment, the nitrile rubber 3305 is produced by the synthetic rubber plant of Lanzhou Petrochemical Company.

[0045] The active zinc oxide is nano-active ZNO produced by Luoyang Lantian.

[0046] The stearic acid is SA-1801 from Wilmar Oil Technology.

[0047] The vulcanization accelerator is a mixture of N-cyclohexyl-2-benzothiazolylsulfonamide (CZ), dibenzothiazyl disulfide (DM), and tetramethylthiuram disulfide (TMTD) produced by Weilin New Materials Technology Co., Ltd. in a weight ratio of 5:3:1.

[0048] The vulcanizing agent is granulated sulfur from Zhongshan Hanxin Rubber and Plastic Material Factory: S-80GEF150.

[0049] The vulcanization accelerator is one of thiazole, thiuram or quaternium accelerators.

[0050] The antioxidant RD and antioxidant 4010NA are produced by Nanjing Chemical Industry Co., Ltd. of Sinopec Group.

[0051] The semi-refined paraffin wax is produced by China National Petroleum Corporation.

[0052] The carbon black reinforcing agent N330 is produced by Shandong Bio Carbon Black.

[0053] The white carbon black is Hengsil-955 produced by Wuxi Hengheng White Carbon Black Co., Ltd.

[0054] The semi-reinforcing carbon black is semi-reinforcing carbon black 774 produced by Kashgar Derik.

[0055] The calcined kaolin is produced by China Kaolin Corporation.

[0056] The light calcium carbonate is produced by Xuancheng Zhuofeng New Materials.

[0057] The softener is acetyl tributyl citrate ATBC produced by Jiangsu Raymond New Materials Co., Ltd.

[0058] Embodiment 2

[0059] A method for preparing a nitrile rubber bright surface rubber plug which is not easy to get a dirty mold, comprising the following steps:

[0060] (1) Use a rubber cutting machine to cut the nitrile rubber 3305 and styrene butadiene rubber 1502 and set aside;

[0061] (2) Add 95 parts of nitrile rubber 3305 and 5 parts of styrene butadiene rubber 1502 to the kneading machine. After plasticating for 60 seconds, lift the pressing mass and add 5 parts of active zinc oxide, 1.5 parts of stearic acid, 1.0 parts of antioxidant RD, 0.5-1.0 parts of antioxidant 4010NA, 1 part of semi-refined paraffin, and 3.5 parts of vulcanization accelerator. After kneading for 60 seconds, lift the upper pressing mass and add 20 parts of carbon black reinforcing agent N 330, 45 parts of semi-reinforced carbon black, 12 parts of white carbon black, 20 parts of calcined kaolin, 20 parts of light calcium carbonate, 25 parts of softener, knead for 60 seconds, raise the pressure weight, after the rubber material is agglomerated, raise the pressure weight once, knead for 60 seconds, clean the dust at the feeding port, add the pressure weight, raise the pressure weight twice in the middle, until the temperature of the mixing chamber rises to 130℃, and then the material is automatically discharged, the total time is about 10 minutes;

[0062] (3) the rubber material of step (2) is discharged on a 22-inch open mill, the roller distance is adjusted to 3 mm, and the material is thinned three times; it is conveyed by a conveyor belt and cooled to below 90° C., 2 to 2.5 parts of a vulcanizing agent are added on a 24-inch open mill, the roller distance is adjusted to 2 mm, and the material is thinned three times. After making two triangular bags, the material is placed on a sheet with a thickness of 7 mm and cooled;

[0063] (4) Take the sample and perform sulfurization at 165℃×8min, test the test piece at 165℃×6min, cool for 16h, and test the physical properties; after meeting the basic requirements of physical properties, according to the thickness required by the mold, 18-inch open mill produces 3-5mm sheets;

[0064] (5) Cut the semi-finished product into a shape according to the width of the semi-finished product required for molding using a strip cutter, and weigh the semi-finished product using an electronic scale;

[0065] (6) Add the semi-finished product into the mold and start vulcanization molding; compression vulcanization molding conditions: temperature 165°C, time 6 minutes, pressure 18 MPa.

[0066] Embodiment 3

[0067] A method for preparing a nitrile rubber bright surface rubber plug which is not easy to get a dirty mold, comprising the following steps:

[0068] (1) Use a rubber cutting machine to cut the nitrile rubber 3305 and styrene butadiene rubber 1502 and set aside;

[0069] (2) Add 92 parts of nitrile rubber 3305 and 8 parts of styrene butadiene rubber 1502 to the kneading machine. After plasticating for 60 seconds, lift the pressing mass and add 4.5 parts of active zinc oxide, 1.2 parts of stearic acid, 0.8 parts of antioxidant RD, 0.8 parts of antioxidant 4010NA, 0.8 parts of semi-refined paraffin, and 3 parts of vulcanization accelerator. After kneading for 60 seconds, lift the upper pressing mass and add 15 parts of carbon black reinforcing agent N3 30, 40 parts of semi-reinforced carbon black, 10 parts of white carbon black, 15 parts of calcined kaolin, 15 parts of light calcium carbonate, 20 parts of softener, knead for 60 seconds, raise the pressure weight, after the rubber material is agglomerated, raise the pressure weight once, knead for 60 seconds, clean the dust at the feeding port, add the pressure weight, raise the pressure weight twice in the middle, until the temperature of the mixing chamber rises to 130℃, and then automatically discharge the material, the total time is about 9 minutes;

[0070] (3) the rubber material of step (2) is discharged on a 22-inch open mill, the roller distance is adjusted to 3 mm, and the material is thinned three times; it is conveyed by a conveyor belt and cooled to below 90° C., 2 to 2.5 parts of a vulcanizing agent are added on a 24-inch open mill, the roller distance is adjusted to 1.3 mm, and the material is thinned three times. After making two triangular bags, the material is placed on a sheet with a thickness of 7 mm and cooled;

[0071] (4) Take the sample and perform sulfurization at 165℃×8min, test the test piece at 165℃×6min, cool for 16h, and test the physical properties; after meeting the basic requirements of physical properties, according to the thickness required by the mold, 18-inch open mill produces 3-5mm sheets;

[0072] (5) Cut the semi-finished product into a shape according to the width of the semi-finished product required for molding using a strip cutter, and weigh the semi-finished product using an electronic scale;

[0073] (6) Add the semi-finished product into the mold and start vulcanization molding; compression vulcanization molding conditions: temperature 165°C, time 6 minutes, pressure 18 MPa.

[0074] Test example:

[0075] The performance of the vulcanized products obtained from the common commercial product (comparative example), Example 1, Example 2, and Example 3 was tested according to the national standard, and the test results are shown in the following table;

[0076]

Claims

1. A nitrile rubber bright surface rubber plug which is not easy to get the mold dirty, characterized in that: The raw material of the nitrile rubber bright surface rubber plug comprises the following components in parts by weight:

2. According to claim 1, a nitrile rubber bright surface rubber plug that is not easy to get the mold dirty, characterized in that: The active zinc oxide is nano-active ZNO.

3. According to claim 1, a nitrile rubber bright surface rubber plug that is not easy to get the mold dirty, characterized in that: The vulcanization accelerator is a mixture of N-cyclohexyl-2-benzothiazolyl sulfenamide, dibenzothiazyl disulfide, and tetramethylthiuram disulfide in a weight ratio of 5:3:

1.

4. According to claim 1, a nitrile rubber bright surface rubber plug that is not easy to get the mold dirty, characterized in that: The vulcanizing agent is sulfur.

5. According to claim 1, a nitrile rubber bright surface rubber plug that is not easy to get the mold dirty, characterized in that: The vulcanization accelerator is a combination of one or more thiazole, thiuram or quaternium accelerators.

6. According to claim 1, a nitrile rubber bright surface rubber plug that is not easy to get the mold dirty, characterized in that: The softener is acetyl tributyl citrate.

7. A method for preparing a nitrile rubber bright surface rubber plug which is not easy to get the mold dirty, characterized in that: The steps include: (1) Use a rubber cutting machine to cut the nitrile rubber 3305 and styrene butadiene rubber 1502 and set aside; (2) Add 90-95 parts of nitrile rubber 3305 and 5-10 parts of styrene-butadiene rubber 1502 to the kneader, and after plasticating for 60 seconds, add 4-5 parts of active zinc oxide, 1-1.5 parts of stearic acid, 0.5-1.0 parts of antioxidant RD, 0.5-1 parts of antioxidant 4010NA, 0.5-1.5 parts of semi-refined paraffin, and 2.5-3.5 parts of vulcanization accelerator. After kneading for 60 seconds, add 10-20 parts of carbon black reinforcing agent N330, 35-45 parts of semi-reinforced carbon black, 8-12 parts of white carbon black reinforcing agent, 10-20 parts of calcined kaolin, 10-20 parts of light calcium carbonate, 15-25 parts of softener ATBC, knead for 60 seconds, raise the pressure weight, after the rubber material is agglomerated, raise the pressure weight once, knead for 60 seconds, clean the dust at the feeding port, add the pressure weight, raise the pressure weight twice in the middle, until the temperature of the mixing chamber rises to 130℃, and then automatically discharge the material, the total time is 8-10 minutes; (3) the rubber material obtained in step (2) is discharged on a 22-inch open mill, the roller distance is adjusted to 2-4 mm, and the material is thinned three times; it is conveyed by a conveyor belt and cooled to below 90° C., 2-2.5 parts of a vulcanizing agent are added on a 24-inch open mill, the roller distance is adjusted to 1-2 mm, and the material is thinned three times. After making two triangular bags, the material is placed on a sheet with a thickness of 6-8 mm and cooled; (4) Take the sample and perform sulfurization at 165℃×8min, test the test piece at 165℃×6min, cool for 16h, and test the physical properties; after meeting the basic requirements of physical properties, according to the thickness required by the mold, 18-inch open mill produces 3-5mm sheets; (5) Cut the semi-finished product into a shape according to the width of the semi-finished product required for molding using a strip cutter, and weigh the semi-finished product using an electronic scale; (6) Add the semi-finished product into the mold for vulcanization molding; the conditions for compression vulcanization molding are temperature 165°C, time 6 minutes, and pressure 18 MPa.